2011
DOI: 10.2165/11596930-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Management of Acute and Persistent Aggression in Forensic Psychiatry Settings

Abstract: Aggressive behaviour is common in forensic psychiatric settings. The aetiology of aggressive behaviour is multifactorial and can be driven by psychosis, impulsivity, psychopathy, intoxication, cognitive impairment, or a combination of all of these. Recognition of the different factors behind the aggression can inform medication selection and the relative need for specific environmental and behavioural interventions in a forensic psychiatric setting. Acute agitation needs to be managed quickly and effectively b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…While pharmacotherapy with neuroleptics and mood stabilizing agents such as anti-epileptics and lithium can be highly effective for certain individuals, it is incompletely effective in many cases [1], persistent use of these agents frequently results in metabolic and movement disorders, and in geriatric patients with dementia, confers increased risk of death [2]. Further, the exact mechanism of action of these agents as they relate to anti-aggressive, or “serenic” activity, is incompletely understood [3]. Investigation of pharmacological mechanisms that reduce aggression but are distinct from currently available agents may lead to novel, increasingly specific treatments for aggression with more favorable side effect profiles, and provide further understanding of the molecular mechanisms regulating aggression.…”
Section: Introductionmentioning
confidence: 99%
“…While pharmacotherapy with neuroleptics and mood stabilizing agents such as anti-epileptics and lithium can be highly effective for certain individuals, it is incompletely effective in many cases [1], persistent use of these agents frequently results in metabolic and movement disorders, and in geriatric patients with dementia, confers increased risk of death [2]. Further, the exact mechanism of action of these agents as they relate to anti-aggressive, or “serenic” activity, is incompletely understood [3]. Investigation of pharmacological mechanisms that reduce aggression but are distinct from currently available agents may lead to novel, increasingly specific treatments for aggression with more favorable side effect profiles, and provide further understanding of the molecular mechanisms regulating aggression.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, evidence has emerged indicating that schizophrenia and violence are related (Fazel et al, ; Citrome and Volavka, ) and that schizophrenia may augment the propensity for interpersonal violence about sevenfold (Tiihonen et al, ). One way of exploring the association between violence and schizophrenia is by looking into subtypes of aggression among people with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…For example, psychotropic medications are generally considered to be part of "standard" forensic rehabilitation; yet, there is an overall poverty of research on their use with MDOs. However, one area that has attracted a considerable amount of research attention concerns the effect of antipsychotic medications on aggressive behavior in patients with schizophrenia, including forensic patients (e.g., Citrome & Volavka, 2011;Krakwoski, Czobor, Citrome, Bark, & Cooper, 2006;Volavka & Citrome, 2008). Several empirical studies have shown that the second generation antipsychotic drug, Clozapine, is effective in reducing aggression among persons with schizophrenia independent of its antipsychotic properties (e.g., Citrome et al, 2001;Krakwoski et al, 2006).…”
Section: Therapies Targeting Mental Illness and Other Psychological Nmentioning
confidence: 99%